2011
DOI: 10.1159/000329007
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Early Integration of Palliative Care into Breast Cancer Therapy. Promoting Disease-Specific Guidelines

Abstract: To comply with patients‘ needs as well as ASCO and WHO recommendations, our institution aims to integrate palliative care (PC) early in the course of breast cancer (BC) therapy. The evaluation of relevant pilot project data revealed that these recommendations were too vague to trigger PC integration. Therefore, a standard operating procedure (SOP) was developed by our interdisciplinary working group to provide disease-specific information to overcome the ambiguity of the WHO recommendations and guide PC integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Traditionally, palliative care has been related to advanced disease and end-of-life care which is reflected in a limited life expectancy [14] or disease-specific criteria for advanced disease [13] as inclusion criteria in some studies, whereas other studies include patients much earlier in the disease trajectories such as newly diagnosed patients but still with incurable disease [17]. Traditionally, palliative care has been related to advanced disease and end-of-life care which is reflected in a limited life expectancy [14] or disease-specific criteria for advanced disease [13] as inclusion criteria in some studies, whereas other studies include patients much earlier in the disease trajectories such as newly diagnosed patients but still with incurable disease [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, palliative care has been related to advanced disease and end-of-life care which is reflected in a limited life expectancy [14] or disease-specific criteria for advanced disease [13] as inclusion criteria in some studies, whereas other studies include patients much earlier in the disease trajectories such as newly diagnosed patients but still with incurable disease [17]. Traditionally, palliative care has been related to advanced disease and end-of-life care which is reflected in a limited life expectancy [14] or disease-specific criteria for advanced disease [13] as inclusion criteria in some studies, whereas other studies include patients much earlier in the disease trajectories such as newly diagnosed patients but still with incurable disease [17].…”
Section: Resultsmentioning
confidence: 99%
“…Hui et al [4 && ] systematically reviewed the oncology literature on terms and definitions of palliative care and supportive care. Gaertner et al [13] developed with local experts a template for palliative care consultations in a This review highlighted the lack of definitional clarity for many important terms in the supportive and palliative oncology literature and called for a need to include a definition within each article that uses the term until standardized definitions exist [4 && ].…”
Section: Review Papers and Consensus Statementsmentioning
confidence: 99%
“…Nevertheless, the recommendation published so far lack more disease-specific information or further details on specific assignments [1,7]. In evaluations preceding this publication, we found that this ambiguity hindered EI in the case of lung and breast cancer [5,8,9]. A concept proposed by the NCCN tries to trigger timely PC integration by the expected survival time, symptom burden, or performance status of the patients [10,11].…”
Section: Limitations Of Existing Recommendationsmentioning
confidence: 99%
“…Although the differences between the groups were not statistically significant, the patients in this series who were not referred to hospice received their last dose of chemotherapy an average of 16 days prior to Whereas the identification of the point in the disease course at which the cancer is clearly ''life-threatening, incurable, or progressive'' may be more intuitive for other solid tumors than for breast cancer due to its variable clinical course and numerous available treatment options, there do exist diseasespecific guidelines for the integration of palliative care into comprehensive breast cancer therapy. 2 In New York State, the Palliative Care Information Act was passed into law in early 2011. 13 This act requires physicians and nurse practitioners to offer terminally ill patients information concerning palliative care and EOL options.…”
Section: Discussionmentioning
confidence: 99%
“…As novel and targeted treatment options continue to be developed and translated to the clinic, survival time is expected to increase further. 2 Compared with other incurable malignancies, patients with metastatic breast cancer have many available and approved treatment options for their disease. Choices for cancer therapy at the end of life (EOL) are increasingly numerous and complex with more options for therapy, higher expectations of therapy, less toxic treatment options, and better supportive care and side-effect management.…”
Section: Introductionmentioning
confidence: 99%